Impact of Digital Media on Character Development and Social Skills Among Primary School Students at Sekolah Indonesia Jeddah - Triastuti Dian Anggraeni; Aprilia Tina Lidyasari; Marwan Marwan; Agus Herwanto (STAI Hubbulwathan Duri, 2025)
The increasing exposure of primary school students to digital media raises concerns about its influence on character development and social skills. This study examines the effects of digital media on students at Sekolah Indonesia Jeddah, focusing on responsibility, empathy, and discipline. Additionally, it explores the role of social-emotional learning (SEL) in mitigating negative effects and enhancing social behaviors. A mixed-method approach was employed, incorporating surveys, interviews, and behavioral observations. Data were collected from primary school students to assess their digital media consumption patterns and their impact on character development and social interactions. Findings reveal a significant relationship between digital media usage and students' character development. Increased screen time was associated with reduced face-to-face interactions, affecting empathy and collaboration. However, structured SEL interventions were found to enhance students’ social skills, promoting responsibility and discipline despite high digital engagement. The study highlights the dual impact of digital media, where excessive usage can hinder interpersonal skills, while controlled exposure, combined with SEL strategies, fosters positive character traits. The integration of SEL into primary education emerges as a key approach to balancing digital consumption and social-emotional development. The findings emphasize the need for a balanced media exposure strategy and SEL integration in primary education to support students' holistic development. Educators and parents should collaborate to regulate media use and implement SEL programs that nurture essential social and emotional competencies.